Synthesis, Growth, and Electrical Transport Properties of Pure and LiSO4-Doped Triglycine Sulphate Crystal - Farhana Khanum; Jiban Podder (International Journal of Optics)
Pure triglycine sulphate (TGS) and LiSO4-doped TGS crystals were grown from aqueous solution by natural evaporation method. The grown crystals were characterized by UV-vis spectroscopy, electrical conductivity (𝜎dc) measurement, dielectric studies, microhardness, and thermogravimetry/differential thermal analysis. Pure TGS and LiSO4-doped TGS crystals were found highly transparent and full faced. The direct current conductivity is found to increase with temperature as well as dopant concentrations. Curie temperature remains the same for pure and doped crystals, but dielectric constant and dielectric loss increase with dopant concentration. The Vicker’s microhardness of the LiSO4-doped TGS crystals along (001) face is found higher than that of pure TGS crystals. Etching studies illustrate the quality of the doped crystal. The experimental results evidence the suitability of the grown crystal for optoelectronic applications.